The Adjustment - Young, Suzanne (Young, Suzanne. Program series, 2017)
When Tatum's boyfriend, Weston, loses his memories of her in The Program, they decide to undergo The Adjustment, where Tatum's memories of their time together are implanted into Weston's mind, but trouble lies ahead when Weston's emotions do not match the experiences.